Lymphoid Interstitial Pneumonia Associated With Hashimoto Thyroid Disease - Steven Tessier; Santo Longo; Livia Bratis; Sudip Nanda; Firas Ido (Annals of Internal Medicine: Clinical Cases)
Lymphoid interstitial pneumonia (LIP) refers to the diffuse infiltration and accumulation of lymphocytes within the alveolar interstitium and may be associated with multiple autoimmune diseases, most notably Sjögren syndrome. Only rare cases of LIP have been reported in patients with Hashimoto thyroiditis. In these cases, the patients also had at least 1 additional autoimmune disease. We report a case of LIP in a 70-year-old woman whose only autoimmune disease was Hashimoto thyroiditis. This case supports the hypothesis that Hashimoto thyroiditis alone may instigate the development of LIP.